Microbial Antigenic Pressure and Evolution of the Immune Response: Toward a Better Understanding of the Human Immune System in Health and Disease and Therapeutic Interventions - Magrone, Thea; Jirillo, Emilio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2010)
The continuous antigenic triggering has greatly contributed to the evolution of the immune system and, therefore, animals have developed cells able to cope with a broad variety of microbial antigens and or their toxins, e.g., endotoxins. At the same time, intestinal commensals have evolved along with human progress and introduction of new foods, thus empowering both regional and systemic immune response. In this review, some important steps in the evolution of the immune system will be analyzed such as organization of lymphoid organs, formation of germinal centers, leukocyte attraction to tissue, function of Toll like receptors and role of antimicrobial peptides. In particular, the major phylogenetic acquisitions of living organisms in the assessment of the immune machinery will be emphasized. Finally, fish will be taken into consideration as animal models of human diseases also in view of drug design strategies. Special attention will be focused on vaccinated salmon and zebrafish models.
Keywords: drug design